THE ROLE OF NOTICING IN DEVELOPING SPEAKING SKILLS - Teshaboyeva Nafisa Zubaydulla qizi; Xamidova Mashxura Abror qizi (Ustozlar uchun, 2025)
In the process of language acquisition, speaking is one of the most critical and complex skills to develop. It involves not only the correct use of grammar and vocabulary but also pronunciation, fluency, and the ability to interact appropriately in different contexts. One cognitive process that plays a significant role in the development of speaking skills is noticing. Schmidt (1990) introduced the concept of noticing, emphasizing that language learners must consciously notice features of the target language to acquire them effectively. This paper explores the role of noticing in the development of speaking skills, its theoretical background, strategies to enhance noticing, and its practical implications for language learning.